Cylindrospermopsin and glyphosate accumulation in lettuce (Lactuca sativa) simultaneously exposed to both toxicants in hydroponic and soil systems - Sengupta, S. (2021)
In nature, the simultaneous occurrence of multiple emergent contaminants such as cyanotoxins (e.g., cylindrospermopsin (CYN)) and herbicides (e.g., glyphosate (GLY)), is highly expectable and it can be anticipated, mainly in the aquatic and terrestrial environments. The use of contaminated water for irrigation can be hazardous to the agricultural sector and some studies have reported that, individually, these contaminants can be accumulated in the edible tissues exerting a negative influence on crop plants safety and ultimately in human health. Furthermore, recent studies have suggested that some cyanotoxins (e.g., microcystins) can change the membrane permeability of roots, resulting in changes in the accumulation rates of other contaminants in plants. Since edible plants are exposed to a wide variety of substances through irrigation water, there is increasing concern in the potential adverse effects of the interactions between those substances when present simultaneously, especially when this can have potential public health consequences. The aim of this study was to determine the accumulation of CYN in Lactuca sativa simultaneously exposed to GLY at environmentally relevant concentrations. Lettuce plants were exposed for 15 days to 50 μg/L or kg of CYN-containing crude extract (Chrysosporum ovalisporum culture - LEGE X001) and 750 μg/L or kg of GLY, in hydroponic and soil systems, respectively. The resins (HP20, SP700, and XAD18) were evaluated for MC-LR uptake kinetics, capacities, and extraction efficiencies and simple procedures were developed for determining MC-LR concentration in binding disc extracts by Adda-ELISA (U.S. EPA Method 546). The XAD18-DGT/Adda-ELISA method had a 7-d deployment time detection limit of ≈0.05 μg/L and capacity of > 250 μg/L of MC-LR in water samples which encompass U.S. EPA and WHO advisory concentrations for drinking and recreational waters. The XAD18DGT/Adda-ELISA method determined timeaveraged MC-LR concentrations in waters with wide ranging pH (4.9–8.3) and ionic strength (0.04–0.8 M) under well-stirred and quiescent conditions with 90–101% accuracy. In addition to high sensitivity and accuracy, the method is simple, inexpensive, and applicable for determining MC-LR and related MCs concentrations in waterbodies with wide ranging chemical characteristics and hydrodynamic conditions. 4.11.07 Cylindrospermopsin and Glyphosate Accumulation in Lettuce (Lactuca sativa) Simultaneously Exposed to Both Toxicants in Hydroponic and Soil Systems S. Sengupta, School of Bio Sciences and Technology Vellore Institute of Technology, Vellore - 632 014, Tamil Nadu, India; M.M. Freitas, School of Health, Polytechnic Institute of Porto; E. Pinto, I. Ferreira, LAQV/REQUIMTE, Departament of Chemical Sciences, Faculty of Pharmacy, University of Porto, Rua Jorge de Viterbo Ferreira 228, 4050313 Porto, Portugal; F. Oliveira, J. Azevedo, CIIMAR - Interdisciplinary Centre of Marine and Environmental Research, University of Porto, Terminal de Cruzeiros do Porto de Leixões, Av. General Norton de Matos, s/n, 4450–208 Porto; A. Prieto, L. Diez-Quijada, A. Jos, A.M. Cameán, Area of Toxicology, Faculty of Pharmacy, Universidad de Sevilla, Profesor García González n◦2, 41012 Seville, Spain / Toxicology; A. Campos, Interdisciplinary Centre of Marine and Environmental Sciences, CIIMAR; V. Vasconcelos, CIIMAR - Interdisciplinary Centre of Marine and Environmental Research, University of Porto, Terminal de Cruzeiros do Porto de Leixões, Av. General Norton de Matos, s/n, 4450–208 Porto In nature, the simultaneous occurrence of multiple emergent contaminants such as cyanotoxins (e.g., cylindrospermopsin (CYN)) and herbicides (e.g., glyphosate (GLY)), is highly expectable and it can be anticipated, mainly in the aquatic and terrestrial environments. The use of contaminated water for irrigation can be hazardous to the agricultural sector and some studies have reported that, individually, these contaminants can be accumulated in the edible tissues exerting a negative influence on crop plants safety and ultimately in human health. Furthermore, recent studies have suggested that some cyanotoxins (e.g., microcystins) can change the membrane permeability of roots, resulting in changes in the accumulation rates of other contaminants in plants. Since edible plants are exposed to a wide variety of substances through irrigation water, there is increasing concern in the potential adverse effects of the interactions between those substances when present simultaneously, especially when this can have potential public health consequences. The aim of this study was to determine the concentration of CYN and GLY in lettuce plants (roots and leaves) was determined by LC/MSMS. The results show that, at the described conditions, CYN was accumulated in roots (0.06-7.62 μg CYN/g Dw) and leaves (0.13-1.1 μg CYN/g Dw) of lettuce, especially when plants were exposed in hydroponic system. However, interestingly, when lettuce plants were exposed simultaneously to both toxicants the concentration of CYN assimilated by lettuce plants (roots and leaves) was respectively, 1.5fold and 1-3-2.2-fold lower than in the exposure to isolated CYN. Conversely, the plants exposed to the mixture in soil system, showed that the concentration of GLY incorporated by lettuce (roots and leaves) was higher than in the exposure to the isolated compound (0.04 - 0.21 µg GLY/g and < LOQ - 0.84 µg GLY/g, respectively). This finding highlights the potential for the enhancement of GLY accumulation in lettuce plants due to their cooccurrence with CYN, and it underlines the importance of further research regarding the mechanism involved.